Problematika Pembelajaran Bahasa Indonesia di Sekolah: Suatu Kajian Literatur - Dedi Febriyanto; Siti Rukiyah; Missriani M (Madani: Jurnal Ilmiah Multidisiplin, 2023)
This study aims to describe various problems in learning Indonesian at school through previous literature.  This study was carried out using qualitative methods with a literature study approach.  The results of the study show that the problems of learning Indonesian in schools are very complex.    Problems that occur in general can be viewed from a policy perspective by the government, institutions, teachers and students.  Viewed from a policy perspective, the curriculum is a central point that is widely criticized, both in terms of content and implementation patterns.  The policies contained in the curriculum are considered to tend to make things difficult for teachers, including Indonesian language teachers.  Viewed from an institutional perspective, in this case quite a few schools ignore the issue of facilities and infrastructure.  Insufficient facilities and infrastructure in schools will more or less affect the level of success of the ongoing learning process.  From the teacher's point of view, professionalism is the main problem.  Lack of teacher professionalism will ultimately give rise to problems from the student side, ranging from low cognitive, affective and psychomotor scores, to problems related to students' low interest in learning.